Association between PTA for milk from foreign Holstein sires and daughters milk yield in Brazil (Research, Society and Development, 2022)
The genetic improvement of the Holstein breed in Brazil is supported by the use of reproductive biotechnologies, mainly due to artificial insemination. Dependent on imported cryopreserved semen, therefore, genetic material from breeders evaluated in different environments, in this way, Brazilian herds seems to be likely to not present satisfactory genetic advances, caused by the phenomenon of genotype-environment interaction. Therefore, this research aims to evaluate whether, when selecting bulls with high genetic merit for milk, they have the potential to generate progenies with superior milk yield (MY). For this, a database of Holstein heifers and cows (n=7,556) was used, containing lactation records and PTA milk data from their sire. Lactations were adjusted for environmental effects and analyzed by Spearman correlation in relation to PTA milk of their respective sire. Significant correlations (p